Notes on the Role of the Teacher in Indigenous School Education1 - Peggion, Edmundo Antônio [UNESP] (My University, 2008)
It is at the intersection between education and culture that lies the central point in a discussion about the educational processes in which indigenous peoples have recently involved themselves. Both terms carry with them an idea of a set of values and traditions, either internal or external, which need to be considered when working with indigennous peoples. Much has been said about indigenous school education, the experiences and results of programmes which are currently being developed in Brazil, but what is the impact of these processes? By virtue of their novelty, there are few systematic studies that address key structural questions.